Legal writing: takeways from the study visit to the William and Mary Law School - Creciun, Natalia (CEP USM, 2024)
The paper presents a brief evaluation of the takeaways emerging from the academic life at William and Mary Law School, Williamsburg, Virginia, USA, focused primarily on the Legal writing course and on the supporting institutional mechanisms for improving the quality of higher education, and for enriching the professional background of future lawyers, under conditions of current global trends. The main findings result from on-site observing of the teaching-learning evaluating process, through interactive and collaborative activities. As a general conclusion the quality of legal higher education can be improved only through multidimensional and intersectoral synergies, including academia, civil society, public authorities, employers. Investments in human resources and in infrastructure, open mindedness in the teaching-learning-evaluating process in legal schools are part of the knowledge management and they really count.

Lucrarea prezintă o scurtă evaluare a concluziilor din viața academică la William and Mary Law School, Williamsburg, Virginia, SUA, focusate, în primul rând, pe cursul de Scriere juridică și pe mecanismele instituționale de sprijin pentru îmbunătățirea calității învățământului superior și pentru îmbogățirea experienței profesionale a viitorilor juriști, în condițiile tendințelor globale actuale. Principalele constatări rezultă din observarea la fața locului a procesului de predare-învățare-evaluare, prin activități interactive și colaborative. Cu titlu de concluzie generală, calitatea învățământului juridic superior poate fi îmbunătățită doar prin sinergii multidimensionale și intersectoriale, care să includă mediul academic, societatea civilă, autoritățile publice, angajatorii. Investițiile în resurse umane și în infrastructură, spiritul deschis în procesulde predare-învățare-evaluare în școlile de drept fac parte din managementul cunoștințelor și într-adevăr contează.
SCRIEREA JURIDICĂ: CONCLUZII DIN VIZITA DE STUDIU LA ȘCOALA DE DREPT WILLIAM AND MARY
Keywords: IRAC; knowledge management; legal writing; IRAC; managementul cunoștințelor; scrierea juridică